Investigating Projectile Penetration of Concrete Blocks Reinforced by Different Material - Mohamed Yassin Ibrahim Laissy (Investigating Projectile Penetration of Concrete Blocks Reinforced by Different Material, 2021)
This work provides an overview of the use of different materials in reinforcing concrete blocks. The state of knowledge in processing, characterization, and the most important properties of the used materials are presented with a particular emphasis on identifying fundamental structure/property. The different methods used for the performance of projectile penetration have been discussed in this review article.